A Comparative Study of Long-Term Results of Buccal Mucosal Graft and Penile Skin Flap Techniques in the Management of Diffuse Anterior Urethral Strictures: First Report in Iran - Hosseini, Jalil; Soltanzadeh, Kaveh (Urology Journal, 2009)
Purpose: To compare Buccal Mucosa Graft with Penile Skin Flap techniques in the management of anterior urethral diffuse strictures longer than 3 cm. Materials and Methods: Thirty seven patients with a mean age of 28.5 (range 5 to 50) years had been treated by these two techniques using the ventral onlay patch from February 1997 to March 2002. Patients’ follow-up included physical examination, history taking, retrograde urethrography, cystoscopy and uroflowmetry at the month six, at the end of the first and the second years, and then yearly if required. Results: These techniques were applied for anterior urethral strictures (bulbar and penile) longer than 3 cm. Buccal mucosal graft (BMG) was used in 18 patients and penile skin flap (PSF) in 19. Mean follow-up was 27.5 (range 6 to 50) months. Mean age was 30.8 Â± 11.8 years for BMG group and 27.8 Â± 15.6 years for PSF group. Urethral stricture etiology, surgery history, and previous endoscopic surgery history were similar in both groups. The stricture site in BMG group was penile in 2 patients (11.1%), bulbar in 8 patients (44.4%), and penobulbar in 8 patients (44.4%). In PSF group the stricture site was penile in 11 patients (57.9%), bulbar in 5 patients (26.3%) and penobulbar in 3 patients (15.8%). Success rate in 6-month follow-up was 93.9% for BUG group and 83% for PSF. By performing dilatation and internal rethrotomy for mild strictures, the success rate with mean follow-up of 27.5 months was 13.8% for BMG group and 78.9% for PSF. Only one patient from BMG developed temporary impotence for about 12 months. Conclusion: BMG and PSF are considered as simple and proper techniques with good long term outcomes in the management of diffuse anterior urethral strictures. These 2 techniques could be applied in patients with history of several surgeries. The results of BMG were better than PSF, still, this difference was not statistically significant.